Curcumin Ameliorates Diabetic Nephropathy by Suppressing NLRP3 Inflammasome Signaling. (17th January 2017) - Lu, Miaomiao; Yin, Nanchang; Liu, Wei; Cui, Xiangfei; Chen, Shuo; Wang, Ermin
Abstract : Diabetic nephropathy (DN) is the leading cause of end-stage renal disease, partly because of the lack of effective treatments for DN. Curcumin has been shown to exert strong antifibrotic effects in DN, but the underlying mechanisms are not well characterized. In this study, we sought to determine the effects of curcumin on diabetic renal disease in db/db mice and characterize the underlying mechanism of action. We administered curcumin to db/db mice for 16 weeks. In comparison to mock-treated db/db mice, curcumin-treated mice showed diminished renal hypertrophy, reduced mesangial matrix expansion, and a lower level of albuminuria. Furthermore, the upregulated protein and mRNA expressions of collagen IV and fibronectin in the renal cortices of the db/db mice were inhibited by curcumin treatment. Additionally, curcumin treatment was associated with significant reductions in mature interleukin-1 β, cleaved caspase-1, and NLRP3 protein levels in the renal cortices of db/db mice as well as in HK-2 cells exposed to high glucose concentration. In summary, curcumin, a potent antifibrotic agent, is a promising treatment for DN, and its renoprotective effects appear to be mediated by the inhibition of NLRP3 inflammasome activity.